2011
DOI: 10.1016/j.ajog.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Methadone and perinatal outcomes: a retrospective cohort study

Abstract: Methadone exposure is associated with an increased risk of adverse perinatal outcomes, even when known adverse sociodemographic factors have been accounted for. Methadone dose at delivery is 1 of the determinants of neonatal abstinence syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 27 publications
3
87
2
1
Order By: Relevance
“…These may be a direct opioid effect but other confounding variables could also have contributed to the observed fetal adverse outcomes. Variables influencing fetal growth and gestational age at delivery include smoking, multiple drug use and low socioeconomic status: all factors being prevalent in SMM in the present and previous studies (Cleary et al;, Fischer & Kopf, 2007, Simpson, 1957. While heroin has been associated with retarded fetal growth (Bada et al 2002, Minnes et al;2011, Minozzi et al;2008), the use of methadone has been shown to be associated with higher birth weights when compared to women who continued to use heroin.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These may be a direct opioid effect but other confounding variables could also have contributed to the observed fetal adverse outcomes. Variables influencing fetal growth and gestational age at delivery include smoking, multiple drug use and low socioeconomic status: all factors being prevalent in SMM in the present and previous studies (Cleary et al;, Fischer & Kopf, 2007, Simpson, 1957. While heroin has been associated with retarded fetal growth (Bada et al 2002, Minnes et al;2011, Minozzi et al;2008), the use of methadone has been shown to be associated with higher birth weights when compared to women who continued to use heroin.…”
Section: Discussionsupporting
confidence: 64%
“…They booked their pregnancy significantly later than the general control population, as has been previously reported in the literature (Cleary et al;, Savona-Ventura, 2004, Thangappah, 2000. Consequently, any medical or obstetric problem arising during pregnancy would be identified and addressed late.…”
Section: Discussionmentioning
confidence: 72%
“…Elevated rates of preterm birth (<37 weeks) at three times national average have been reported, as well as low birth weight (<2500 g), admission to neonatal intensive care [3] and need for extended treatment for Neonatal Abstinence Syndrome, which afflicts from 45% to 94% of newborns [4]. The effects of opioid dependence can have synergistic deleterious effects when they are in conjunction with other problems of drug using pregnant women including medical problems, sexually transmitted diseases, psychiatric disorders and polysubstance abuse [5].…”
Section: Introductionmentioning
confidence: 99%
“…Methadone-exposed babies have demonstrated reduced birth weight and head circumference, prematurity, [21] and rates of neonatal withdrawal syndrome ranging from 46% [22] to 97% [12,23]. A dose-response relationship between methadone and neonatal abstinence syndrome (NAS) has been reported in a large series of 618 women [24] but a meta-analysis by the same author [23] and others [25] did not confirm these findings. A recent prospective study by this group concluded that neonates exposed to methadone doses ≥ 80 mg required higher cumulative doses of morphine treatment for NAS but attributed this to concomitant use of other drugs [26].…”
Section: Introductionmentioning
confidence: 99%
“…A recent prospective study by this group concluded that neonates exposed to methadone doses ≥ 80 mg required higher cumulative doses of morphine treatment for NAS but attributed this to concomitant use of other drugs [26]. Increased rates of congenital anomalies have been reported in nonrandomized studies, [12,24,27] but these have not yet been evaluated in randomized designs [28] capable of controlling for concomitant consumption of other substances.…”
Section: Introductionmentioning
confidence: 99%